Describing and Comparing Protein Structures Using Shape Strings - Shu, Nanjiang; Hovmoller, Sven; Zhou, Tuping (Current Protein and Peptide Science, 2008)
Different methods for describing and comparing the structures of the tens of thousands of proteins that have been determined by X-ray crystallography are reviewed. Such comparisons are important for understanding the structures and functions of proteins and facilitating structure prediction, as well as assessing structure prediction methods. We summarize methods in this field emphasizing ways of representing protein structures as one-dimensional geometrical strings. Such strings are based on the shape symbols of clustered regions of φ/Ψ dihedral angle pairs of the polypeptide backbones as described by the Ramachandran plot. These one-dimensional expressions are as compact as secondary structure description but contain more information in loop regions. They can be used for fast searching for similar structures in databases and for comparing similarities between proteins and between the predicted and native structures.
Keywords: structure comparison